A Bibliometric Analysis of Pesantren's Educational Impact: Insights from The Scopus Database (1994–2022) - Gazali, Erfan; Budiana, Agnes Arum (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study used bibliometric techniques to evaluate pesantren's academic output. It aimed to decipher trends in pesantren study themes, collaborative authorship networks, the most prolific contributors, frequently cited papers, and prominent affiliations publishing pesantren-centric works from 1994 to 2022. Design/methods/approach – Utilizing Scopus as the primary data source with the keyword